Inhibition of miMOMP-induced SASP to combat age-related disease - Liao, Xiaoli; Guo, Zhennan; He, Mouhai; Zhang, Yichun (Frontiers in Aging, 2025)
Cellular senescence, first described in 1961, was initially observed in normal human fibroblasts that ceased proliferating after a finite number of divisions in culture. This process is triggered by various stimuli, including oxidative stress, chromatin modifications and oncogene activation, characterized by irreversible cell-cycle arrest, resistance to apoptosis and the induction of a complex senescent associated secretory phenotype (SASP). Over the past decade, emerging evidence has linked cellular senescence to the aging process and a wide range of chronic age-related diseases. Consequently, research focused on targeting senescence to alleviate or delay age-related disease, referred to as senotherapy, has been conducted rapidly. Therefore, elucidating the mechanisms of cellular senescence is essential for providing practical strategies aimed at addressing this condition.